ANALISIS PEMELIHARAAN MESIN SLUDGE SEPARATOR DENGAN PENDEKATAN RELIABILITY CENTERED MAINTENANCE (RCM): (Studi Kasus: PT. XXX) - Kurniawan, Iwan; Sidiq, Ahmad Zamakhsyari Sidiq; Aripin, Wahyu Teri (LPPM Sekolah Tinggi Teknologi Cipasung, 2025)
Maintenance is an action to repair or prevent machine damage. Smooth production processes are demands that must be met so that company targets can be achieved. This happens due to damage to the machine or waiting for the ordered unit/parts to arrive to replace the damaged spare part. As a result, the agreed product completion time is not met. This study was conducted on the Sludge Separator machine by calculating the value of the damage rate function, the reliability function of critical components during production under certain conditions and periods. The data collected are data on the use of spare part damage data throughout 2021 and 2022 and the purchase price per unit of spare parts, therefore, to solve this problem, planned maintenance (corrective maintenance) is needed with a reliability approach. The data is processed using the reliability method by applying the Weibull distribution damage rate function to determine the amount of critical component inventory over a period of two years. The results of the study show that critical components are distributed Weibull. Based on the critical components that have been determined by the Weibull method over a period of two years for each critical component is the Bowl Spindle component as many as 3 units of optimal order (Q*) = 1 unit/order reorder point (r) = 1 unit) paring Disc as many as 2 units (Q* = 1 unit/order, r = 1 unit) 2.6546, Friction Pad & Screw as many as 4 units (Q* = 3 units/order, r = 1 unit) = 1.5576 V Nozzle Q 1.60 mm 3 units (Q* = 1 unit/order, r = 1 unit) = 2.0970.